2000
DOI: 10.3923/pjbs.2000.1305.1307
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Influence of Sunflower (Helianthus annuus) on Germination and Seedling Growth of Linseed (Linum usititatissimum)

Abstract: Allelopathic influence of aqueous extracts of sunflower on linseed, germination and seedling growth have been evaluated. It was found that linseed's, germination, seedlings, fresh and dry weights and roots and shoots lengths were increased at 25% concentration. These parameters showed decrease with the increase in the concentrations at 50, 75 and 100% treatment. The chemical analysis also indicated that seedlings grown in 25% sunflower aqueous extract had higher protein, potassium, phosphorus and starch conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In recent years, it has become also, evident that a large number of compounds extracted from weeds and crops significantly were toxic to living cell and organisms. Park andMoody (1991 andMehboob et al, 2000) indicated that sunflower (Helianthus annuus L.),among several crops, exhibits a strong allelopathic property. Naseem (1997) reported that the incorporation of whole sunflower plants or (roots + leaves) showed more suppressive effect on weed density and dry matter accumulation.…”
mentioning
confidence: 99%
“…In recent years, it has become also, evident that a large number of compounds extracted from weeds and crops significantly were toxic to living cell and organisms. Park andMoody (1991 andMehboob et al, 2000) indicated that sunflower (Helianthus annuus L.),among several crops, exhibits a strong allelopathic property. Naseem (1997) reported that the incorporation of whole sunflower plants or (roots + leaves) showed more suppressive effect on weed density and dry matter accumulation.…”
mentioning
confidence: 99%